A proof of concept gene‐activated titanium surface for oral implantology applications. (4th March 2020) - Laird, Noah Z.; Malkawi, Walla I.; Chakka, Jaidev L.; Acri, Timothy M.; Elangovan, Satheesh; Salem, Aliasger K.
Abstract: Dental implants are very successful medical devices, yet implant failures do occur due to biological and mechanical complications. Peri‐implantitis is one such biological complication that is primarily caused by bacteria and their products at the implant soft tissue interface. Bacterial infiltration can be prevented by the formation of a reliable soft tissue seal encircling dental implants. Platelet‐derived growth factor‐BB (PDGF‐BB) has significant chemotactic and proliferative effects on various mesenchymal cell types, including fibroblasts, and therefore can be an effective molecule to enhance the peri‐implant soft tissue seal. To overcome the limitations of the recombinant protein form of PDGF‐BB, such as cost and the need for supraphysiological doses, we have developed and characterized a titanium surface that is rendered bioactive by coating it with polyethylenimine‐plasmid DNA (pDNA) nanoplexes in the presence of sucrose. Human embryonic kidney 293T (HEK293T) cells and human primary gingival fibroblasts (GFs) were successfully transfected in culture with enhanced green fluorescent protein ( EGFP )‐encoding pDNA or platelet‐derived growth factor subunit B ( PDGFB )‐encoding pDNA loaded into nanoplexes and coated onto titanium disks in a dose‐dependent manner. GFs were shown to secrete PDGF‐BB for at least 7 days after transfection and displayed both minimal viability loss and increased integrin‐α2 expression 4 days posttransfection.